An explosion accident analysis of the laboratory in university. Issue 4 (30th March 2020) - Chen, Mengmeng; Wu, Yaqin; Wang, Kai; Guo, Haijun; Ke, Wei
Abstract: Academic research in the laboratory is often considered as the work with lower risks compared with other process industries. Whereas, it is revealed that there are still many accidents happening in the laboratory, causing deaths, injuries, and economic losses. In order to identify the main causes and improve the safety management, an explosion accident in a laboratory of a university is thoroughly investigated based on the 24Model and 5Whys method. The results indicate that inadequate safety knowledge and insufficient safety awareness of the experimenters serve as main contributors of the accident. In order to effectively prevent such accidents, it is necessary to strengthen the safety training of the experimenters and associated technical managers, so as to create a good safety culture atmosphere in the university. Moreover, a smart safety management system based on internet of things (IoT) is established for the laboratory, which contains equipment management subsystem, experiment consumables management subsystem, personnel management, training and assessment subsystem, environmental monitoring subsystem, and accident diagnosis subsystem. With the help of the system, daily safety of the laboratory can be greatly improved.